Schiff-base derived chitosan impregnated copper oxide nanoparticless: an effective photocatalyst in direct sunlight - Narayanan, V. Sathiya; Prasath,K., P. Varun; Ravichandran, K.; Easwaramoorthy, D.; Shahnavaz, Zohreh; Mohammad, Faruq; Al-Lohedan, Hamad A.; Paiman, Suriati; Won, Chun Oh; Sagadevan, Suresh (Elsevier, 2020)
In this work, highly efficient photocatalytic degradation of bentazone herbicide was demonstrated using Schiff-base derived chitosan (ChdSb)/copper oxide (CuO) nanoparticles (NPs). For the formation of ChdSb/CuO NPs, chitosan's derivatization with 1-hydroxy-2-acetonaphthone was initiated first, followed by the impregnation of CuO NPs. The formed composite was thoroughly characterized by making use of many different techniques for the surface morphology, conjugation/coating, optical properties, crystal nature, and its size, etc. Following the physical characterization, the photocatalytic performance of ChdSb/CuO NPs tested in the presence of sterilized buffers of 4, 7, and 9 and direct sunlight in the winter season indicated for improved catalytic activity. The observation of such photocatalytic activity can be due to the shift in bandgap energy from 2.12 to 2.45 eV which caused the trapping of OH radicals by the holes in the valence band to further produce a powerful oxidizing agent. Also, with the help of various other substrates like benzoic acid, azide ion, acrylamide, rose bengal, and triphenylphosphine, we confirmed for the involvement of OH radicals in the photocatalytic activity. Besides, the p-nitroacetophenone-pyridine (PNAP/PYR) used as an actinometer helped to determine the quantum yield of bentazone hydrolysis. The observed half-life and rate constant of bentazone photocatalytic degradation in buffer solutions at different pHs of 4, 7, and 9 were found to be (1.31 & 0.53), (0.88 & 0.79), and (0.89 & 0.79), respectively. Similarly, the quantum yields for the bentazone photocatalytic degradation in the mentioned buffers were found to be 2.72 × 10-7, 3.31 × 10-7, and 4.14 × 10-7 M respectively. From the comparison of results, the degradation rate of bentazone in these buffers was found to be increasing in the order of pH 9 = pH 7 > pH 4. On testing of the reproducibility, we found that the prepared nanocomposite can be utilized for at least six times without any loss to its photocatalytic activity and thereby confirming for the potential role in sustainable degradation of herbicides and other industrial dyes.